Helix-mediated over 1 nm-range chirality recognition by ligand-to-ligand interactions of dinuclear helicates. Issue 25 (26th May 2021) - Suko, Natsumi; Itamoto, Hideki; Okayasu, Yoshinori; Okura, Naoya; Yuasa, Junpei
Abstract : Long-range chirality recognition between the two chiral guest ligands can be tuned based on the helix distances ( d Ln–Ln = 11.5 and 14.0 Å) of bis-diketonate bridged dinuclear lanthanide complexes (2Th and 3Th, respectively). Abstract : Long-range chirality recognition between the two chiral guest ligands can be tuned based on the helix distances ( d Ln–Ln = 11.5 and 14.0 Å) of bis-diketonate bridged dinuclear lanthanide complexes (2Th and 3Th, respectively) used as mediators. Both 2Th and 3Th form one-dimensional (1D) helical structures upon terminal binding of two chiral guest co-ligands (L R or L S ). Long-range chiral self-recognition is achieved in self-assembly of 2Th with L R and L S to preferentially form homochiral assemblies, 2Th -L R ·L R and 2Th -L S ·L S, whereas there is no direct molecular interaction between the two guest ligands at the terminal edges. X-ray crystal structure analysis and density functional theory studies reveal that long-range chiral recognition is achieved by terminal ligand-to-ligand interactions between the bis-diketonate ligands and chiral guest co-ligands. Conversely, in self-assembly of 3Th with a longer helix length, statistical binding of L R and L S occurs, forming heterochiral (3Th -L R ·L S ) and homochiral (3Th -L R ·L R and 3Th -L S ·L S ) assemblies in an almost 1 : 1 ratio. When phenyl side arms of the chiral guest co-ligands are replaced by isopropyl groups (L′ R and L′ S ), chiral self-recognition is also achieved in the self-assembly process of 3Th with the longer helix length to generate homochiral (3Th -L′ R ·L′ R and 3Th -L′ S ·L′ S ) assemblies as the favored products. Thus, subtle modification of the chiral guests is capable of achieving over 1.4 nm-range chirality recognition.